On Intentional Relations, Intentional Contexts and E. Huserl’s Phenomenology - Norkus, Zenonas (Problemos, 1987)
Consciousness is treated intentionally as a system of subject-world relations having two features, namely, that of dependence upon the mode of conceiving the object, and that of independence from its real existence. Because of these features difficulties arise in the application of the rules of extensional logic to the statements on intentional relations (intentional contexts). Husserl’s conception of intentionality can be compared to the semantics of possible worlds for the propositional altitudes as proposed by J. Hintikka. Those correspondences and parallels presuppose the implicit usage of the semantic analogies for the conceptualisation of the introspective data in the conceptions of intentionality.